Innovative technologies for dependable OTS-Based Critical Systems : Challenges and Achievements of the CRITICAL STEP Project - Cotroneo, Domenico; Cotroneo, Domenico (Springer Milan, 2013)
The demand for large-scale dependable, systems, such as Air Traffic Management, industrial plants and space systems, is attracting efforts of many word-leading European companies and SMEs in the area, and is expected to increase in the near future.  The adoption of Off-The-Shelf (OTS) items plays a key role in such a scenario. OTS items allow mastering complexity and reducing costs and time-to-market; however, achieving these goals by ensuring dependability requirements at the same time is challenging. CRITICAL STEP project establishes a strategic collaboration between academic and industrial partners, and proposes a framework to support the development of dependable, OTS-based, critical systems. The book introduces methods and tools adopted by the critical systems industry, and surveys key achievements of the CRITICAL STEP project along four directions: fault injection tools, V&V of critical systems, runtime monitoring and evaluation techniques, and security assessment.